The participation of RANK, RANKL and OPG in tumor osteolysis - Marcin Stanisławowski (Postępy Higieny i Medycyny Doświadczalnej, 2009)
It was recently shown that physiological bone remodeling depends on the dynamic balance of two cytokines that are predominantly secreted by osteoblasts. RANKL promotes the differentiation of osteoclastic precursors and the activation of osteoclasts, whereas osteoprotegerin (OPG) inhibits RANKL action. During the development of many tumors, enhanced osteolysis results in pathological bone destruction. Tumor-associated osteolysis is characterized by the degradation and inhibition of osteoprotegerin (OPG) and increased RANKL expression and secretion by tumor tissue. The resulting RANKL/OPG imbalance causes increased generation and activation of osteoclasts and, finally, a significant decrease in bone mass and pathological bone fractures. Tumor cells may also produce many other factors which affect the RANK/RANKL/OPG system and accelerate osteolysis, including IL-1, IL-6, TNF, and MIP-1α. The elucidation of the key mechanisms of tumor osteolysis has led to clinical trials of biological therapies based on the inhibition of RANKL and stimulation of OPG activity.